2015
DOI: 10.1002/chem.201502143
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Redox Properties of a Nonheme Iron(III)–Peroxo Complex Binding Redox‐Inactive Zinc Ions by Water Molecules

Abstract: Redox-inactive metal ions play important roles in tuning chemical properties of metal–oxygen intermediates. Herein we report the effect of water molecules on the redox properties of a nonheme iron(III)–peroxo complex binding redox-inactive metal ions. The coordination of two water molecules to a Zn2+ ion in (TMC)FeIII-(O2)-Zn(CF3SO3)2 (1-Zn2+) decreases the Lewis acidity of the Zn2+ ion, resulting in the decrease of the one-electron oxidation and reduction potentials of 1-Zn2+. This further changes the reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…20 By utilizing this natural rule, Lee et al first reported the synthesis of a nonheme iron(III)-peroxozinc(II) complex and redox behaviors of the complex. 21 They confirmed that the rate of O−O bond cleavage decreases as the Lewis acidity of Zn 2+ at the active sites is lowered, 21 which agrees with the results of previous reports. However, the effects of Zn 2+ on heterogeneous OER catalysts have not yet been clarified.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…20 By utilizing this natural rule, Lee et al first reported the synthesis of a nonheme iron(III)-peroxozinc(II) complex and redox behaviors of the complex. 21 They confirmed that the rate of O−O bond cleavage decreases as the Lewis acidity of Zn 2+ at the active sites is lowered, 21 which agrees with the results of previous reports. However, the effects of Zn 2+ on heterogeneous OER catalysts have not yet been clarified.…”
Section: Introductionsupporting
confidence: 88%
“…In some other enzymes, Zn 2+ polarizes the P–O or C–O bonds to increase the activity . By utilizing this natural rule, Lee et al first reported the synthesis of a nonheme iron­(III)-peroxo-zinc­(II) complex and redox behaviors of the complex . They confirmed that the rate of O–O bond cleavage decreases as the Lewis acidity of Zn 2+ at the active sites is lowered, which agrees with the results of previous reports.…”
Section: Introductionsupporting
confidence: 83%
“…Metal superoxo, peroxo, and hydroperoxo species are key intermediates in the activation of dioxygen by metal complexes, and studies of the interaction of LAs with these species would be of fundamental interest. Indeed, a number of reports in this area have recently appeared. …”
Section: Discussionmentioning
confidence: 99%
“…[20] Many works have shown that the use of core-shell Fe@Fe 2 O 3 nanowire as a heterogeneous catalyst can accelerate the Fe + 2 /Fe + 3 cycle, resulting in higher yields of different Fenton processes at higher pHs. [1,3,8,12,21] In addition to core-shell Fe@Fe 2 O 3 nanowire, as one of the most efficient Fenton heterogeneous catalysts, some of the other iron structures such as Iron-Peroxo complex, [22] Fe 2 O 3 -pillared rectorite, [23] Cu-Doped Fe@Fe 2 O 3 core-shell nanoparticle, [24] Pd/PdO/Fe 2 O 3 nanoparticles [25] and Fe 2 O 3 /TiO 2 nanoparticles [26] and so on were applied in Fenton degradation of organic pollutants. Also, there have been a few recent reports about iron-based MOFs in Fenton removal of some organics, [27,28] but so far there have been no reports of the Fenton degradation surfactants using MOF compounds.…”
Section: Introductionmentioning
confidence: 99%